Alumni Relations at the Heart of Philanthropy: Exploring volunteering and volunteer management opportunities - Gallo, Maria L. (ICAReAlumni Conference Proceedings, 2019)
‘Friend-raising before Fundraising’ is a common phrase used in advancement work, implying that building relationships with alumni within our Higher Education Institutions is a pre-cursor to the ultimate effort of securing donations. In this keynote presentation, I hope to dispel this myth and demonstrate why Alumni Relations in and of itself is at the heart of philanthropy, in particular, through the interface of alumni and volunteering efforts. Throughout this interactive and energising session, I present academic and professional research literature, in both alumni relations and volunteer management, to show the central place of Alumni Relations to realise the philanthropic aims of our institutions. Philanthropy comes from the Greek ‘for the love of humanity’ and it is from this simple definition that Alumni Relations can reclaim its prominent and rightful place at the core of philanthropic work. Philanthropy concentrates on the giving of time, talent, treasure and ties, all of which can be fostered effectively through Alumni Relations. This “4Ts” framework also reveals the role of volunteer management programmes and engaging alumni as volunteers in a strategic, concerted and diffused way across our institutions. We will explore, through research evidence and case studies, the ways that these “4Ts’ of philanthropy promoted through volunteering can build the 4Is: interdependence, integration, identity and inherence, for lifelong value to our institution and especially for our alumni community. By the end of the session, we reflect on the following questions: What key strategies can I undertake—the small steps— to raise the profile and value of Alumni Relations as the heart of philanthropy within my institution? And, how can I enhance my volunteering initiatives to maximise the time, talent, treasure and ties by and for my alumni community?